1973
DOI: 10.1128/aac.3.6.662
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Minocycline and Tetracycline by Tetracycline-Susceptible and -Resistant Bacteria

Abstract: Minocycline (7-dimethylamino-6-demethyl-6-deoxytetracycline) is a new semisynthetic tetracycline with potent activity against tetracycline-susceptible bacterial pathogens and unique activity against tetracycline-resistant staphylococci. Studies to determine the basis for this unique activity showed that, whereas tetracycline-resistant staphylococci took up less 3H-tetracycline than the susceptible cells, both the tetracycline-resistant and -susceptible cells accumulated equivalent amounts of "C-minocycline. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1975
1975
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…Resistance to tetracyclines in S. aureus has been shown to be correlated with a decreased uptake of tetracycline (Sompolinsky et al 1970;Kuck & Forbes, 1973). The strains studied by these two groups were invariably those in which resistance was determined by plasmidborne genes.…”
Section: S Aureus Tetracycline Resistance I39mentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to tetracyclines in S. aureus has been shown to be correlated with a decreased uptake of tetracycline (Sompolinsky et al 1970;Kuck & Forbes, 1973). The strains studied by these two groups were invariably those in which resistance was determined by plasmidborne genes.…”
Section: S Aureus Tetracycline Resistance I39mentioning
confidence: 99%
“…However, the semi-synthetic tetracycline, minocycline (7-dimethylamino-6-deoxytetracycline), has been reported to be active against many tetracyclineresistant strains of staphylococci (Fedorko, Katz, & Allnoch, 1968 ; Kuck & Forbes, I 973 ; Leigh & Simmons, 1974). Kuck & Forbes (1973) showed that a tetracycline-resistant, minocycline-sensitive strain of S. aureus, with a decreased uptake of tetracycline, continued to accumulate minocycline at an undiminished rate. Schaefler & Francois (1973) found that some tetracycline-resistant strains of staphylococci could mutate to resistance to minocycline.…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of plasmid-mediated tetracycline resistance in these bacteria are similar, in that resistance is usually inducible (Izaki, Kiuchi & Arima, 1966;Franklin, 1967;Sompolinsky et al 1970a Asheshov, 1975), and appears to result from decreased uptake of the antibiotic (Izaki et al 1966;Franklin, 1967;De Zeeuw, 1968;Sompolinsky et al 1g7oa;Avtalion et al 1971; Kuck & Forbes, 1973;Shipley & Olsen, 1974).…”
mentioning
confidence: 99%
“…No such mutants could be obtained spontaneously or by mutagenesis from cells harboring the extrachromosomal tet resistance marker. The cause of the difference in resistance spectrum is not known, although differences in the accumulation of the two compounds could be at least partly responsible (17,33). Our inability to obtain minocycline-resistant mutants from a large number of S. aureus strains of the Tc phenotype could be explained by the requirement for a double mutation, a VOL.…”
Section: Methodsmentioning
confidence: 84%
“…Experiments of Kuck and Forbes (17) with E. coli and Sompolinsky and Krausz (33) with S. aureus indicate that tetracycline-resistant cells which retain their susceptibility to minocycline show a decreased accumulation of tetracycline but retain the ability to accumulate minocycline. Resistance to both tetracycline and minocycline determined by some R factors (29,31) is accompanied by a decrease in the accumulation of both tetracycline and minocycline (17).…”
mentioning
confidence: 99%